Post cardiac surgery sternal wound sepsis burden, risk factors and outcomes at Red Cross War Memorial Children’s Hospital, Cape Town, South Africa: A five-year experience - Mpisane, F.; Brooks, A.; Basera, W.; Zuhlke, L.J. (SA Heart Journal, 2020)
Purpose: Sternal wound infection (SWI) is associated with significant morbidity and mortality in post-operative cardiac patients. We aimed to describe the burden, risk factors and outcomes of SWI in post-operative paediatric cardiac patients at a tertiary children’s hospital. Methods: We conducted a retrospective record review of cardiac surgeries via median sternotomy over a 5-year period to identify cases of SWI. Results: Between 2011 and 2016, 1 319 patients underwent median sternotomy. Thirty four (2.6%) patients developed SWI; 18 (13%) patients developed deep sternal wound infection (DSWI), and 16 (12%) developed superficial sternal wound infections (SSWI). Twenty two (16%) of SWIs were apparent within a week postsurgery before discharge, and the remaining were readmitted post-discharge. Seven (0.5%) patients died from complications. Conclusion: Significant morbidity was associated with SWI. Furthermore, with a mortality rate of 20% in the case of DSWI, we strongly support quality improvement procedures such as the Sternal Wound Prevention Bundle (SWPB) that was introduced in late 2014. However, the rate of SWI implies that ongoing monitoring and evaluation of the SWPB is necessary and more stringent adherence to the protocol may result in better outcomes.